Mechanistic Understanding of the Palmitoylation of Go Protein in the Allosteric Regulation of Adhesion Receptor GPR97 - Hao Zhang; Guojun Chu; Gaoming Wang; Min Yao; Shaoyong Lu; Ting Chen (MDPI AG, 2022)
Adhesion G-protein-coupled receptors (aGPCRs)-a major family of GPCRs-play critical roles in the regulation of tissue development and cancer progression. The orphan receptor GPR97, activated by glucocorticoid stress hormones, is a prototypical aGPCR. Although it has been established that the palmitoylation of the C-terminal Go protein is essential for Go's efficient engagement with the active GPR97, the detailed allosteric mechanism remains to be clarified. Hence, we performed extensive large-scale molecular dynamics (MD) simulations of the GPR97−Go complex in the presence or absence of Go palmitoylation. The conformational landscapes analyzed by Markov state models revealed that the overall conformation of GPR97 is preferred to be fully active when interacting with palmitoylated Go protein. Structural and energetic analyses indicated that the palmitoylation of Go can allosterically stabilize the critical residues in the ligand-binding pocket of GPR97 and increase the affinity of the ligand for GPR97. Furthermore, the community network analysis suggests that the palmitoylation of Go not only allosterically strengthens the internal interactions between Gαo and Gβγ, but also enhances the coupling between Go and GPR97. Our study provides mechanistic insights into the regulation of aGPCRs via post-translational modifications of the Go protein, and offers guidance for future drug design of aGPCRs.